PENGARUH MOTIVASI, KOMPENSASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI BANK SYARIAH MANDIRI CABANG DARMO SURABAYA - Kusumaningrum, Dini (GEMA EKONOMI, 2016)
at the agency Bank Syariah Mandiri Darmo Surabaya comes to influence of motivation, compensation and corporate culture to employee performance. This phenomenon indicates that the performance of agency Bank Syariah Mandiri Darmo Surabaya much influenced by variables motivation, compensation and corporate culture.Based on the result of research conducted showed that after testing using Multiple Linier Regresion, that the three independent variables consisting of motivation, compensation and corporate culture together (simultaneously) have an influence on the performance of agency Bank Syariah Mandiri Darmo Surabaya. This can be seen from correlation coefficient (R) of Multiple Linier Regresion model of 0.745 indicating a strong relationship between the three independent variables siultaneously on the performance of employees.F test result proved that three is significant influence between the variables of motivation (X1), compensation (X2) and corporate culture (X3) on the determination (R2) = 0.556 indicates that 55.6 % Bank Syariah Mandiri Darmo Surabaya agency employee are influenced by third independent variables. While the result of t test of cempetence of each variable motivation (X1), compensation (X2) and corporate culture (X3) partially affect the performance of agency employees Bank Syariah Mandiri Darmo Surabaya. Compensation variable (X2) has the most dominant influence on the performance of ageny employees Bank Syariah Mandiri Darmo Surabaya.